Advertising: from creation to dissemination - Alves, Cátia Sofia Carvalheiro (2021)
This dissertation is an investigation of different factors that affect advertising performance. Chapter 1 introduces the importance of studying advertising effectiveness by exploring its production and dissemination. Chapter 2 examines how brand attitudes of advertising creatives (hereinafter “creatives”) change the type of executional elements they choose to include in their advertisements. Chapter 3 extends Chapter 2 by exploring how advertising creatives’ brand attitudes alter their ability to forecast the extent to which consumers will like their work. Chapter 4 focuses on the impact of discrete contextual emotions on the memorability of subsequent advertisements. Chapter 5 summarizes the findings of each chapter and highlights theoretical and practical contributions.